ANALISIS PERBEDAAN TUGAS DAN FUNGSI LEMBAGA PEMASYARAKATAN ANAK (LAPAS ANAK) DENGAN LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) DALAM SISTEM PERADILAN PIDANA ANAK DI INDONESIA - Hafiz Adri Sanjaya; Sukmareni Sukmareni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Adjustment to the nomenclature and name of the Child Correctional Institution (LAPAS Anak) to become the Special Child Development Institution (LPKA); not only in the form of the formation of a new organization, but also in the realization of the transformation of handling children in conflict with the law (ABH) in Indonesia.This change in the nomenclature above certainly causes some differences in terms of arrangements, duties and functions, scope of authority, forms of guidance carried out and others between Children’s Prison and Children's Special Development Institution. The formulation of the problems raised in this study “How are the differences in the duties and functions of fostering correctional inmates between Children’s Prison and Children's Special Development Institution. in the Indonesian criminal justice system.This research is a normative legal research, using secondary data as the main data in the form of regulations related to Child Correctional Institutions and Special Child Guidance Institutions, obtained through library research (document study), using qualitative analysis in drawing research conclusions.Research findings “The difference in duties and functions of fostering correctional inmates between Children’s Prison and Children's Special Development Institution. in the Indonesian criminal justice system, can be seen in several ways, including the basic nomenclature, principles, duties, functions, especially the coaching function. Correctional Students, The right of children to obtain education and teaching, skills training, community guidance, alleviation of children, food and beverage management, distribution of equipment, and child health services in the context of personal development in accordance with their interests, talents and level of intelligence. Children's Special Development Institution., changes to the institution and is based on the direction of guidance based on their rights, namely the right to survival, growth and developmentKeywords: Differences, Duties and Functions, Guidance, Children's Prison, Children's Special Development Institution